ACTORS AND NORMS IN AN ISLAMIC MARRIAGE: A Study of Madura Community in Rural Eastern East Java (JOURNAL OF INDONESIAN ISLAM, 2019)
This article is concerned about everyday practice of marriage in religious community of Sumbersari, in Pasuruan, East Java. It analyses how actors and norms are involved to shape the practice. It also relates them to individual agencies of the couples. Materials of this article are based on my fieldwork that I did in early 2017. In this article, I suggest that the ideas of an ideal marital spouse are generally conceptualised in the set of localised notions of chastity (kesucian), good manner (apik), and good fortune (mompong) that necessarily culminate in the identity as santri (pious muslim). However, the implementation of these ideas are much dependent upon the roles of pelantar (traditional matchmaker) who mediates the communication of the two families concerned. In addition to pelantar, kyai (muslim cleric) is indeed important in the production of an Islam-based legal norm to control sexual morality that sometimes confronts against the state legal norm. Increasing participation in formal education and the rise of women’s mobility have challenged this pattern. Girls have an autonomy to choose her preferred partner. Mutual love becomes more important, although the decision of marriage timing sometimes still belongs to the parents’ authority.